Vitamin D and Its Potential Interplay With Pain Signaling Pathways - Habib, Abdella M.; Nagi, Karim; Thillaiappan, Nagendra Babu; Sukumaran, VijayaKumar; Akhtar, Saghir (Frontiers in Immunology, 2020)
About 50 million of the U.S. adult population suffer from chronic pain. It is a complex disease in its own right for which currently available analgesics have been deemed woefully inadequate since ~ 20% of the sufferers derive no benefit. Vitamin D, known for its role in calcium homeostasis and bone metabolism, is thought to be of clinical benefit in treating chronic pain without the side-effects of currently available analgesics. A strong correlation between hypovitaminosis D and incidence of bone pain is known. However, the potential underlying mechanisms by which Vitamin D might exert its analgesic effects are poorly understood. In this review, we discuss pathways involved in pain sensing and processing primarily at the level of dorsal root ganglion (DRG) neurons and the potential interplay between Vitamin D, its receptor (VDR) and known specific pain signalling pathways including Nerve growth Factor (NGF), glial-derived neurotrophic factor (GDNF), epidermal growth factor receptor (EGFR) and opioid receptors. We also discuss how Vitamin D/VDR might influence immune cells and pain sensitization as well as review the increasingly important topic of vitamin D toxicity. Further in vitro and in vivo experimental studies will be required to study these potential interactions specifically in pain models. Such studies could highlight the potential usefulness of Vitamin D either alone or in combination with existing analgesics to better treat chronic pain.